Analysis of the Effect of Attraction, Expertise, Interaction, Image Satisfaction, and Advertising Trust on Purchase Intention in Social Media Influencer Marketing on Erigo Consumers in Indonesia - Nanda Adelia Permadani; Arif Hartono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
A new digital marketing tool that is emerging today is social media influencer marketing. Social media influencers are individuals who can give consumers perceptions about a brand or product through photos, videos, and other updates on social media platforms such as Twitter, Instagram, Tiktok, Facebook, WhatsApp. This study is an attempt to identify the influence of various attributes of social media influencers on their attractiveness, expertise, interaction, image satisfaction and advertising trust and ultimately on consumer purchase intentions in marketing social media influencers in Indonesia. An online questionnaire was used to collect data via Google Forms and the sample size quota sampling technique was used, and structural equation modeling via PLS-SEM was used for data analysis. This study has as many as 190 respondents. The criteria for respondents in this study were followers of influencer Arief Muhammad, who made up most of Erigo's consumers who were followers of influencer Arief Muhammad. The findings reveal that attractiveness, expertise, and interaction have a significant direct effect on image satisfaction and advertising trust. In addition, consumer purchase intention in social media influencer marketing is directly influenced by the influencer's image satisfaction and advertising trust.